Opposition-sooty tern algorithm for fuzzy control optimization of an inverted pendulum system - Ahmad Nor Kasruddin, Nasir; Mohd Falfazli, Mat Jusof; Nor Maniha, Abdul Ghani; Raja Mohd Taufika, Raja Ismail (Institute of Electrical and Electronics Engineers Inc., 2022)
This paper presents a novel Opposition-Sooty Tern Algorithm (OSTA) which is an improved version of the original Sooty- Tern Optimization Algorithm (STOA). An opposition scheme is incorporated into the STOA structure. This is to enhance the exploration and exploitation of all searching agents throughout a feasible search area. In solving a real-world problem, the algorithm is applied to optimize parameters of a fuzzy logic model for controlling cart's position and pendulum's angle of an inverted pendulum system. Result of the optimization test shows the OSTA has a better accuracy performance compared to its predecessor algorithm. For controlling the inverted pendulum, both OSTA and STOA acquired sufficiently good control performance for the system. However, the fuzzy control scheme optimized by OSTA has resulted in a better tracking and control performance for both cart's position and pendulum's angle.